After Adam Smith : A Century of Transformation in Politics and Political Economy - Milgate, Murray; Stimson, Shannon C. (Book collections on Project MUSE., 2009)
Few issues are more central to our present predicaments than the relationship between economics and politics. After Adam Smith looks at how politics and political economy were articulated and altered in the century following the publication of Smith's Wealth of Nations. It considers how grand ideas about the connections between individual liberty, free markets, and social and economic justice sometimes attributed to Smith are as much the product of gradual modifications and changes wrought by later writers. Thomas Robert Malthus, David Ricardo, James Mill, John Stuart Mill, and other liberals.